Idiopathic scoliosis: Static analysis of the influence of shim use on postural angles - Silva, Jaqueline Santos (2017)
AbstractIntroduction: Scoliosis is characterized as a three-dimensional deformity. In this scenario, the use of shims can promote correction of postural imbalances.Objective: To verify the static changes associated with unilateral manipulation of shims in idiopathic scoliosis.Methods: Two experimental groups composed of participants with scoliosis with double and single curves, and a control group of participants without scoliosis. 10 reflective markers were used, filmed for 15 seconds in the static position in three conditions (no shim; low shim of 1 cm, and high shim of 3 cm) on the right and left foot. The following postural angles were calculated: alpha 1, alpha 2, alpha 3, and alpha 4.Results: There were differences in the shim condition between the control group (CG) and experimental scoliosis with “S” (GES) for alpha 2 and 4 and Scoliosis “C” (GEC) for alpha 2. For shims under the right foot, there were differences between the control group and GES for alpha 4 and the GEC for alpha 1, 2 and 4, and between shims for the GES for alpha 3 and 4. Shims under the left foot were responsible for significant differences between the control group and the GES and GEC groups.Conclusion: These static postural changes indicate that scoliosis curves show adaptability and postural reorganization in response to manipulation with shims, and the greatest influence is seen in the lower segments, both in simple and double curves. According to the results it is concluded that residual scoliotic curvatures have flexibility that allows postural adjustment with shims.